2015
DOI: 10.1155/2015/747961
|View full text |Cite
|
Sign up to set email alerts
|

One-Stop Clinic Utilization in Plastic Surgery: Our Local Experience and the Results of a UK-Wide National Survey

Abstract: Introduction. “See and treat” one-stop clinics (OSCs) are an advocated NHS initiative to modernise care, reducing cancer treatment waiting times. Little studied in plastic surgery, the existing evidence suggests that though they improve care, they are rarely implemented. We present our experience setting up a plastic surgery OSC for minor skin surgery and survey their use across the UK. Methods. The OSC was evaluated by 18-week wait target compliance, measures of departmental capacity, and patient satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Qualitative studies using patient questionnaires in a range of specialities have suggested high patient satisfaction with ‘one-stop’ clinics compared with traditional outpatient encounters 183 , 184 . A study investigating patient experiences with a one-stop haematuria clinic and a clinical pathway containing several visits showed high patient satisfaction (recorded through a questionnaire), reporting that 82% of the participants expressed preference for a one-stop clinic model 183 .…”
Section: A New Model For Men’s Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies using patient questionnaires in a range of specialities have suggested high patient satisfaction with ‘one-stop’ clinics compared with traditional outpatient encounters 183 , 184 . A study investigating patient experiences with a one-stop haematuria clinic and a clinical pathway containing several visits showed high patient satisfaction (recorded through a questionnaire), reporting that 82% of the participants expressed preference for a one-stop clinic model 183 .…”
Section: A New Model For Men’s Healthmentioning
confidence: 99%
“…A study investigating patient experiences with a one-stop haematuria clinic and a clinical pathway containing several visits showed high patient satisfaction (recorded through a questionnaire), reporting that 82% of the participants expressed preference for a one-stop clinic model 183 . A separate study 184 investigated the effects of a one-stop clinic for minor skin surgery in 32 UK plastic surgery departments, reporting that the use of one-stop clinics was associated with a higher degree of patient satisfaction (95% versus 72%) than conventional pathways and improved compliance with 18-week waiting time targets (95% versus 85%).…”
Section: A New Model For Men’s Healthmentioning
confidence: 99%
“…In the face of increasing referral numbers, lengthy waiting times for skin cancer surgery have been reported . Departments with increasing workloads without commensurate increases in resources must develop innovative means of ensuring effective, cost‐efficient treatment in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…‘See and Treat clinics’, also known as ‘one‐stop clinics’, enable specialist assessment and surgical treatment of skin cancers to occur in a single visit . Such clinics are being implemented around the world in attempts to reduce cancer treatment time . Confining assessment and treatment to a single visit benefits patients by reducing the number of appointments required.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, this improves the times patients must wait and reduces the number of hospital visits. One stop clinics have already been established in gynaecology, 9 urology, 10 breast surgery, 11 plastic surgery, 12 ear nose and throat surgery, 13 gastroenterology, 14 care of the elderly 15 as well as in orthopaedic surgery. 16 17 …”
Section: Introductionmentioning
confidence: 99%